ANALISIS KEBIJAKAN RELOKASI PEDAGANG KAKI LIMA ( K5 ) DI TROTOAR JALAN PROTOKOL KOTA LHOKSEUMAWE - Ferizaldi Ferizaldi (Sekolah Tinggi Ilmu Administrasi Nasional, 2022)
The number of street vendors along the Lhokseumawe city protocol road is growing and is a major annoyance to motorists. In addition to utilizing road pavements, they also use the road's edge (shoulder) as a selling location; consequently, road congestion frequently causes traffic jams. This study aims to examine alternative policies that are suitable for addressing these issues. The research methodology employed is the qualitative description. The effectiveness of a policy is determined by analyzing its technical feasibility, ecological feasibility, social feasibility, and economic feasibility. Based on the above evaluation of the alternatives, the results indicated that the alternative policy was to construct an integrated hawker center at KP3 Lhokseumawe with public facilities such as parking, children's playgrounds, prayer rooms, and restrooms. It would also connect to the city's traditional market and the beach recreation area. This policy was chosen as the one most likely to be used because it has a high chance of working.